2014
DOI: 10.1088/1612-2011/11/11/115805
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced stimulated emission of Rhodamine 6 G in nanoporous alumina

Abstract: Properties of stimulated emission of Rhodamine 6 G in porous alumina matrix have been investigated. The characteristics of stimulated emission were examined upon excitation of the samples by second harmonic of Nd: YAG laser in the longitudinal form. It is established that when the pumping source power is equal to 0.38 MW cm−2 on the background spectrum of laser-induced fluorescence the narrow strip of the stimulated emission with a peak wavelength of 566 nm appears. Further increase in the power density of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The porosity and pore density of the nanoporous alumina using the FESEM images are obtained as 8% and 2 × 10 10 /cm 2 and these values are quite close to the reported values in literature [22,23]. The surface area and porosity of the nanoporous alumina using the Brunauer-Emmet-Teller (BET) analysis were reported to be 6 m 2 /g and 0.016 cm 3 /g respectively [24,25]. These values of surface area and porosity of the nanoporous alumina using the BET analysis are very small compared to the surface area (231 m 2 /g) and porosity (0.23 cm 3 /g) of the mesoporous alumina as reported by Patra et al [26].…”
Section: Characterisation and Analysis Of Nanoporous Alumina Microtubessupporting
confidence: 85%
“…The porosity and pore density of the nanoporous alumina using the FESEM images are obtained as 8% and 2 × 10 10 /cm 2 and these values are quite close to the reported values in literature [22,23]. The surface area and porosity of the nanoporous alumina using the Brunauer-Emmet-Teller (BET) analysis were reported to be 6 m 2 /g and 0.016 cm 3 /g respectively [24,25]. These values of surface area and porosity of the nanoporous alumina using the BET analysis are very small compared to the surface area (231 m 2 /g) and porosity (0.23 cm 3 /g) of the mesoporous alumina as reported by Patra et al [26].…”
Section: Characterisation and Analysis Of Nanoporous Alumina Microtubessupporting
confidence: 85%
“…2D NAA-PCs in the form of slabs developed by Masuda and Yokoyama achieved outstandingly high-quality factors, with values of ∼6838 and ∼6333, respectively. Although 1D NAA-GIFs achieve lasing qualities 1 order of magnitude lower, these PCs provide higher lasing quality than that reported for other 2D NAA-based organic solid-state incoherent random lasing systems, with maximum Q LE and G LE values of ∼125 and ∼10.4, respectively, and a maximum Q LE · G LE value of ∼536. Unfortunately, lasing emissions from 1D NAA-DBRs developed by Yang and co-workers were not characterized and thus a comparison with that study is not possible .…”
Section: Results and Discussionmentioning
confidence: 59%
“…An alternative approach to overcome this limitation is functionalizing the inner surface of NAA-PCs with layers of light-emitting materials . Masuda and co-workers realized the first organic solid-state lasing systems from model 2D NAA-PC slabs by modifying their inner surface with composite gain medium layers of fluorophores and dendrimersbranched polymeric molecules. These organic solid-state PC structures yield lasing emissions (LEs) with subnanometric bandwidth (i.e., ∼0.08 nm) and giant quality factor (i.e., ∼6330). However, demonstrations of lasing emissions from NAA-based PC structures are still limited to a few studies. 2D NAA-PC lasing systems suffer from two main constraints: (i) coupling and collection of light at the cross section of thin slabs are challenging and (ii) a constrained range of pore diameter and interpore distance within self-organized regimes. In contrast to their 2D counterparts, 1D NAA-PCs would provide more flexible platforms to develop solid-state lasing systems since (i) the range of lattice constant (period length) can be engineered with precision across the broad spectrum from UV to IR (ii) and more forms of NAA-based PC architectures can be realized (e.g., microcavities, DBRs, GIFs, BSBRs) to harness distinct types of light–matter interactions (e.g., light confinement and recirculation, slow light, hybrid plasmonic–photonic modes).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies by Masuda and co-workers demonstrated slow photon-based organic–inorganic solid-state lasing systems using model 2D NAA slabs functionalized with fluorophores and dendrimers. The PSB of 2D NAA photonic crystals can enhance spontaneous emission by increasing the radiative rate of the gain medium (i.e., fluorophore molecules) through alteration of the dispersion or density of states of emitted photons at the red edge of the PSB (i.e., dielectric component of the porous photonic crystal). Although slow photon lasers based on NAA slabs showed outstanding quality factors (i.e., ∼6330) and ultranarrow bandwidths (i.e., ∼0.08 nm), coupling excitation and the collection of emitted light at the cross section of these thin slabs is challenging. Alternative approaches have focused on the development of distinct forms of RLs combining NAA and organic fluorophores. In these systems, the characteristics of lasing can be engineered in a cavity-free structure by tuning the density of states of the electromagnetic emission through the structural engineering of nanopores (scattering centers). NAA-based RLs (NAA-RLs) also provide operational simplicity because optical excitation and the collection of emitted light can be performed perpendicularly to the cross section of the NAA thin film.…”
Section: Introductionmentioning
confidence: 99%